Parallel Changes in Harvey-Bradshaw Index, TNFα, and Intestinal Fatty Acid Binding Protein in Response to Infliximab in Crohn's Disease. (23rd October 2017) - Al-Saffar, Anas Kh.; Meijer, Carl Hampus; Gannavarapu, Venkata Ram; Hall, Gustav; Li, Yichen; Diaz Tartera, Hetzel O.; Lördal, Mikael; Ljung, Tryggve; Hellström, Per M.; Webb, Dominic-Luc
Abstract : Intestinal fatty acid binding protein (I-FABP) indicates barrier integrity. Aims: determine if I-FABP is elevated in active Crohn's disease (CD) and if I-FABP parallels anti-TNF α antibody (infliximab) induced lowering of TNF α and Harvey-Bradshaw Index (HBI) as potential indicator of mucosal healing. I-FABP distribution along human gut was determined. Serum from 10 CD patients collected during first three consecutive infliximab treatments with matched pretreatment and follow-up samples one week after each treatment and corresponding HBI data were analyzed. I-FABP reference interval was established from 31 healthy subjects with normal gut permeability. I-FABP and TNF α were measured by ELISA; CRP was measured by nephelometry. Healthy tissue was used for I-FABP immunohistochemistry. Pretreatment CD patient TNF α was 1.6-fold higher than in-house reference interval, while I-FABP was 2.5-fold higher, which lowered at follow-ups. Combining all 30 infusion/follow-up pairs also revealed changes in I-FABP. HBI followed this pattern; CRP declined gradually. I-FABP was expressed in epithelium of stomach, jejunum, ileum, and colon, with the highest expression in jejunum and ileum. I-FABP is elevated in active CD with a magnitude comparable to TNF α . Parallel infliximab effects on TNF α, HBI, and I-FABP were found. I-FABP may be useful as an intestine selective prognostic marker in CD.